Thermodynamic characterization of a macrocyclic Zika virus NS2B/NS3 protease inhibitor and its acyclic analogs. Issue 4 (8th December 2022) - Hammerschmidt, Stefan J.; Huber, Simon; Braun, Niklas J.; Lander, Marc; Steinmetzer, Torsten; Kersten, Christian
Abstract: Cyclization of small molecules is a widely applied strategy in drug design for ligand optimization to improve affinity, as it eliminates the putative need for structural preorganization of the ligand before binding, or to improve pharmacokinetic properties. In this work, we provide a deeper insight into the binding thermodynamics of a macrocyclic Zika virus NS2B/NS3 protease inhibitor and its linear analogs. Characterization of the thermodynamic binding profiles by isothermal titration calorimetry experiments revealed an unfavorable entropy of the macrocycle compared to the open linear reference ligands. Molecular dynamic simulations and X‐ray crystal structure analysis indicated only minor benefits from macrocyclization to fixate a favorable conformation, while linear ligands retained some flexibility even in the protein‐bound complex structure, possibly explaining the initially surprising effect of a higher entropic penalty for the macrocyclic ligand. Abstract : Improved ligand affinity from macrocyclization is usually accompanied by favorable binding entropy due to conformational preorganization of the ligand. The entropic penalty observed in macrocyclization of the Zika virus protease inhibitors studied here was elucidated by isothermal titration calorimetry, molecular dynamic simulations, and X‐ray crystallography, showing that the macrocyclic ligand is impaired by rigidification while the linear counterparts retain some of their flexibility within the binding site.